Elevate the masses : Alexander Gardner, photography, and democracy in nineteenth-century America - Best, Makeda, 1975- (The Pennsylvania State University Press, 2020)
"Examines the work of the photographer Alexander Gardner and explores transatlantic dialogues in American Civil War-era photography, demonstrating the concern over issues such as photography as a documentary form, the meaning of democracy, and the impact of industrialization on labor and social relations"--